Влияние осадков на уровень радиационного фона приземной атмосферы - Черепнев М. С. Максим Святославович; Кондратьева А. Г. Алла Георгиевна; Мишина Н. В. Наталия Витальевна; Нагорский П. М. Петр Михайлович; Яковлева В. С. Валентина Станиславовна (2015, 2015)
Заглавие с экрана